2009
DOI: 10.1189/jlb.0209050
|View full text |Cite
|
Sign up to set email alerts
|

Secondary necrosis of apoptotic neutrophils induced by the human cathelicidin LL-37 is not proinflammatory to phagocytosing macrophages

Abstract: Cathelicidins are CHDP with essential roles in innate host defense but also more recently associated with the pathogenesis of certain chronic diseases. These peptides have microbicidal potential and the capacity to modulate innate immunity and inflammatory processes. PMN are key innate immune effector cells with pivotal roles in defense against infection. The appropriate regulation of PMN function, death, and clearance is critical to innate immunity, and dysregulation is implicated in disease pathogenesis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 56 publications
2
18
1
Order By: Relevance
“…In vivo modelling is required to evaluate the efficacy of such an approach, but the observation that antiviral activity is retained by a truncated peptide demonstrates the potential to develop shorter synthetic analogues for future testing. Interestingly, our evaluation of these previously characterised [24] partial peptides representing the N-terminus (amino acids 1–22), a central portion (amino acids 12–33) and the C-terminus (amino acids 16–37) of LL-37 suggests that the antiviral activity may relate to the same core peptide region previously identified for antibacterial activity [24], [40] and for the capacity to induce secondary necrosis of apoptotic cells [41].…”
Section: Discussionmentioning
confidence: 69%
“…In vivo modelling is required to evaluate the efficacy of such an approach, but the observation that antiviral activity is retained by a truncated peptide demonstrates the potential to develop shorter synthetic analogues for future testing. Interestingly, our evaluation of these previously characterised [24] partial peptides representing the N-terminus (amino acids 1–22), a central portion (amino acids 12–33) and the C-terminus (amino acids 16–37) of LL-37 suggests that the antiviral activity may relate to the same core peptide region previously identified for antibacterial activity [24], [40] and for the capacity to induce secondary necrosis of apoptotic cells [41].…”
Section: Discussionmentioning
confidence: 69%
“…Intriguingly, the ability of LL-37 C8 and LL-37 C12,15 to lyse neutrophils and erythrocytes was different. Neutrophil membranes are zwitterionic and interact with LL-37 independently of the overall charge of the peptide [22,39]. By contrast, the erythrocyte membrane contains sialic acid, which results in a negatively charged cell surface; therefore, it is more susceptible to lysis by cationic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent studies show that LL-37 has a direct effect on the cells and might be hemolytic [20] or cytotoxic to peripheral blood mononuclear cells (PBMCs) at high concentrations [21]. At low concentrations (<5 μM), LL-37 induces rapid secondary necrosis of apoptotic human neutrophils [22]. To prevent collateral tissue damage due to exacerbation of inflammation, the activity of LL-37 is strictly controlled by serum proteins [23], most likely apolipoprotein-A1 (apoA-1) [24].…”
Section: Introductionmentioning
confidence: 99%
“…The role of LL‐37 to regulate pathogen‐induced inflammation is now well established . In addition, recent studies have also demonstrated that partial fragments of LL‐37, including the peptide IG‐19, can suppress bacterial endotoxin‐induced inflammatory cytokines . However, the role of LL‐37 and its derivatives in regulating sterile inflammation has not been well defined.…”
Section: Discussionmentioning
confidence: 99%